How to Achieve Sustainable Building Design and Operation with Building Information Modeling - عمران, جمال (Latakia University Journal -Engineering Sciences Series, 2020)
The goal of the research is the combination of sustainable design strategies in BIM tools (Building Information Modeling). By integrating a BIM model into a sustainable planning strategy, specific sustainability trade-off analyzes can be carried out taking into account the actual building conditions and characteristics. In terms of engineering and sustainability, BIM is a newer technology. Many of the tools that measure the impact of old or new sustainable design strategies are not directly available in a BIM model itself. Therefore, data must be exported to another application or imported from a data source. Research offers a new means of improving the quality of life for the Syrian community and a new tool to reduce the negative impact we as humans have on the environment.